Optical Properties of Buffers and Cell Culture Media for Optofluidic and Sensing Applications - Van Thuy Hoang; Grzegorz Stępniewski; Karolina H. Czarnecka; Rafał Kasztelanic; Van Cao Long; Khoa Dinh Xuan; Liyang Shao; Mateusz Śmietana; Ryszard Buczyński (Applied Sciences, 2019)
Interactions between light and various cells in cultures, such as bacteria or mammalian cells, are widely applied for optical sensors and optofluidic systems. These microorganisms need to be kept in proper aqueous media, referred to as buffers or cell culture media, that are required, respectively, for stable storage or delivering biochemical nutrients for their growth. When experiments or numerical analyses on optical devices are performed, the properties of these media are usually considered to be similar to those of pure water, with negligible influence of biochemical compounds on the medium’s optical properties. In this work, we investigated the transmission, material dispersion, and scattering properties of selected and widely used buffers and cell culture media. We show that the optical properties of these media may significantly vary from those of water. Well-defined properties of buffers and cell culture media are essential for proper design of various optical sensing or future optofluidic systems dealing with biological structures.